Legal Regulations for Digital Insurance in Commercial Transactions in the Technology-Based Economy Era - Katili, Nabila (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study examines the implementation of fundamental insurance principles within digital insurance (insurtech) models and the readiness of Indonesian commercial law regulations in responding to technological transformation. The development of insurtech introduces efficiency and broader access to risk protection; however, policy digitalization, algorithm-based underwriting, and automated claims may weaken the application of the principles of insurable interest, indemnity, and uberrimae fidei if not accompanied by legally recognized digital verification and documentation mechanisms. The findings indicate that insurance regulations and POJK 3/2024 on financial sector technological innovation remain general in nature and have yet to regulate specific issues such as smart contracts, definitions of digital loss, data governance, and electronic dispute resolution. Therefore, adaptive regulatory reform is required through sectoral insurtech regulations, classification of digital intermediaries, recognition of electronic evidence, Online Dispute Resolution (ODR) mechanisms, and regulatory sandboxes. This study recommends establishing a responsive legal framework grounded in legal certainty to support digital insurance innovation while strengthening consumer protection.